Pemberdayaan Paguyuban Sanggar Wuni Kreasi Pemanfaatan Sabut Kelapa “Coconut Fiber” sebagai Produk Kebutuhan Rumah Tangga Ramah Lingkungan di Kelurahan Tegal Ratu Kecamatan Ciwandan Kota Cilegon - Ipah Ema Jumiati; Nurul Anriani (Universitas Mathla'ul Anwar Banten, 2022)
COMMUNITY EMPOWERMENT OF SANGGAR WUNI CREATIVE UTILIZATION OF COCONUT FIBER AS AN ENVIRONMENTALLY FRIENDLY HOUSEHOLD NECESSITY PRODUCT IN TEGAL RATU VILLAGE, CIWANDAN DISTRICT, CILEGON CITY. The coconut fiber is a product of coconut husks. Coconut coir is a component of coconut fruit which if used properly can become a product needed by the domestic market and become a product that has a high export value. Ciwandan District is an area that has many large capital-intensive industries. Human Resources (HR) of local communities are considered not yet qualified to compete at the level of high-ranking officials who have policies. Both mentally and in knowledge compared to immigrants who are educationally and knowledgeable superior to the local community. Friction between migrants and local communities always arises when there is a new factory through the recruitment of workers. Local people think that only people far away can work because there are people inside. Meanwhile, 'natives' find it difficult to get to work because there are no insiders. This issue continues to this day. The problem of unemployment in capital-intensive industrial locations became the subject of discussion at Sanggar Wuni Kreasi. Various formulations such as the development of Small and Medium Enterprises (SMEs) are a long-term solution to this problem. Sanggar Wuni Kreasi which is a community that carries out community empowerment activities starting from the fields of education, economy, art, and others.